Elemen Pembentuk Makna pada Sebuah Interior Arsitektur - Dila Hendrassukma (Bina Nusantara University, 2012)
Along with the increasing needs of the community, also increasing the need for space to accommodated those needs. With limited space available nowadays, it is not uncommon to change the old buildings’ function as a place to meet the social growing need of the space. However, it is must be remembered by architects and interior architects when changing the functions of a space that the old space has its own histories and particular meaning to people who had ever occupied it. Those histories and meanings should be included in the creation of the new function. Article gives and describes elements that need to be known in order to understand the sense of a space, such as drawing plans, scale, proportion, movement, transition and access that embodied in the architecture and interior space. Qualitative methods by literature study is used in the making of this article..